Kedudukan Ahli Waris Pengganti (Plaatsvervulling) Dalam Memperoleh Harta Waris Menurut Hukum Islam - Safryan Dilapanga, Mohamad Mirzalino; Astati, Desti; Nurjannah, Eva (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
Introduction to the Problem: Substitute heirs have problems in the form of their implementation in Islamic Law which is rooted in the unclear existing rules, this is based on the status of the successor heirs in obtaining inheritance rights from heirs who have died are not known in the type of inheritance distribution. In Islam, as the successor heir still has direct blood ties (nasab), siblings, and partners in the marriage bond (husband / wife) of the deceased heirs. know clearly and completely, regarding the position of a substitute heir fundamentally in obtaining the inheritance obtained from the rights of a person who has died. Design / Methodology / Approach: Through KHI as tangible as Presidential Instruction No.1 of 1991 contains provisions regarding the position of the successor heirs, so that it becomes the basic instrument for the author in determining legal rules and forms of legal rules for replacement heirs in terms of distribution of appropriate inheritance with Islamic law. Findings: In their existence incapable of not being able to provide a more detailed form of clarity regarding the position of the successor heir which has the character of